PENGARUH PELATIHAN DAN KOMUNIKASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN “KSP PONDOK SARI” - I Ketut Sudana; Ni Luh Putu Yesy Anggreni; Putu Siti Firmani (Jurnal Ilmiah Satyagraha, 2024)
A cooperative is an organization formed on the basis of common interests. We can see whether a cooperative is healthy or unhealthy from the performance of its management and employees. In order to increase the competency of cooperative employees, training is needed that can increase competency. So that the management and employees in the cooperative become competent in their fields. Apart from that, communication between leaders, employees and customers is something that cannot be separated. To obtain good work productivity, of course communication must be established well, so that the work atmosphere becomes comfortable.The research entitled "The Effect of Training and Communication on the Work Productivity of "KSP Pondok Sari" Employees aims to find out: (1) To find out the significant influence of Training on the Work Productivity of "KSP Pondok Sari" Employees, (2) To find out the significant influence of Communication on the Work Productivity of "KSP Pondok Sari" Employees. Work Productivity of "KSP Pondok Sari" Employees, and (3) To determine the significant influence of Training and Communication together on the Work Productivity of "KSP Pondok Sari" Employees. The data analysis technique used is linear regression of two predictors. To find out whether the influence of the independent variable on the dependent variable is real, testing is carried out by carrying out regression analysis, namely analysis of the variance of the regression line to find the F value of the regression line, which can then be tested whether the F value is significant or not, then look for the Relative Contribution (SR) of each - each predictor X1 and The research subjects were "KSP Pondok Sari" with the research object being "KSP Pondok Sari" as many as 10 people.Based on the results of the prediction analysis of two predictors, namely, X1 (training) and With (N-m-1) in this case db = 7/2 with a significance level of 5%, the Ftable value is 4.74. This means that the regression line analyzed is significant as a basis for predictions because there is a significant contribution between the criteria (Y) and the predictors (X1, X2). The Relative Contribution (SR) in % of each predictor is: Predictor X1 = 45.26%, and Predictor Based on these results, the regression line is 28.06%, which consists of the effective contribution of the predictor X1 (training) = 12.70%. And the effective contribution of predictor X2 (communication) = 15.36. Meanwhile, the remaining 71.94% is influenced by other factors.Based on the results of the analysis above, it is hoped that employees can increase their work productivity by participating in training and learning to communicate well. Be it communication with customers/consumers, co-workers and even leaders.